2014
DOI: 10.7150/jca.7797
|View full text |Cite
|
Sign up to set email alerts
|

FGF10: Type III Epithelial Mesenchymal Transition and Invasion in Breast Cancer Cell Lines

Abstract: Purpose: Fibroblastic growth factor-10 (FGF-10) has an important role in type I epithelial mesenchymal transition (EMT) during the embryonic period of life (gastrulation). Since EMT has a critical role during cancer cells invasion and metastasis (type III) this study sought to investigate the possible role of FGF-10 in type III EMT by monitoring breast cancer cell lines' behavior by FGF-10 regulation.Methods: MCF-7 and MDA-MB-231 cell lines with different levels of FGF10 expression were treated with FGF-10 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 43 publications
4
44
0
Order By: Relevance
“…Our previous study showed that FGF-10 is effective in EMT induction through the alteration of epithelial and mesenchymal markers in breast cancer cell lines. This confirms the significance of this EMT inducer in EMT type 3 (Abolhassani et al, 2014[1]). …”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our previous study showed that FGF-10 is effective in EMT induction through the alteration of epithelial and mesenchymal markers in breast cancer cell lines. This confirms the significance of this EMT inducer in EMT type 3 (Abolhassani et al, 2014[1]). …”
Section: Introductionsupporting
confidence: 82%
“…EMT type 1 happens during the early stages of life and is related to gastrulation and development (Shirkoohi, 2013[37]). The important role of FGF-10 in EMT type 1 has previously been reported (Abolhassani et al, 2014[1]), being vital for the appropriate development of stomach, duodenum and cecum in mice (Sala et al, 2006[33]). EMT type 2 is related to tissue regeneration and organ fibrosis, while EMT type 3 is pivotal during cancer progression and metastasis (Kalluri and Weinberg, 2009[20]).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…As a specific ligand of FGFR2 and one of FGF family, FGF10 had been proved to be associated with the progression and prognosis in many kinds of cancers, including breast cancer, lung cancer, and bladder cancer (Chung and Koh 2013;Abolhassani et al 2014;Suzuki et al 2015). Moreover, the oncogenic role of FGF10 paracrine signaling pathway has been revealed (Itoh and Ohta 2014).…”
Section: Discussionmentioning
confidence: 99%
“…FGF10 knockdown siRNA and scrambled siRNA were purchased from Santa Cruz Company (sc-39462) according to previous report (Abolhassani et al 2014). Transfection of siRNA into gastric cancer cells was performed with reagent RNAiMAX (Invitrogen Company, USA) according to the manual.…”
Section: Fgf10 Knockdown and Transfectionmentioning
confidence: 99%